Haemostatic and Lipid Determinants of Prothrombin Fragment F1.2 and D-dimer in Plasma - MacCalum, Peter K.; Cooper, Jackie A.; Martin, Janet; Howarth, David J.; Meade, Thomas W.; Miller, George J. (Thrombosis and Haemostasis, 2000)
The determinants of plasma levels of prothrombin fragment F1.2 (F1.2) and D-dimer in different populations are unclear and this may complicate their interpretation as predictors of thrombotic risk, particularly in the case of D-dimer. We therefore measured F1.2 and D-dimer levels together with a number of other haemostatic and lipid variables in a cross-sectional community-based study of 150 healthy adults (73 male, 77 female), age range 23-80 years, identified from the list of a general practice by stratified random sampling within sex and decade of age. Plasma F1.2 was significantly higher in females than males and was independently and positively associated with age, factor VII activity (FVIIc) and C1 inhibitor, and inversely associated with high density lipoprotein (HDL) cholesterol. Plasma D-dimer showed a quadratic association with age (p <0.0001). In those ≤55 years D-dimer was inversely associated with dilute clot lysis time (DCLT) and activated protein C (APC) ratio. In those >55 years it was significantly higher in females than males and associated positively with age, fibrinogen and, in males, activated factor XII (FXIIa). In a multiple-linear model which combined both age groups, F1.2 and D-dimer were independently associated with each other (r = 0.22, p = 0.03). Thus, thrombin generation and fibrin turnover/fibrinolysis are associated in healthy subjects. HDL cholesterol (inversely) and FVIIc are associated with basal thrombin generation (i.e. F1.2). Determinants of D-dimer differ according to age and interpretation of the biological significance of D-dimer levels in epidemiological studies may therefore not be straightforward.
Keywords: Haemostatic system; coagulation; fibrinolysis; prothrombin fragment F1.2; D-dimer